Un-Habitat Perspectives On Urban Sustainability: The Case Of Saidawa Neighborhood In Erbil City - Sanar Sardar Sami (Eurasian Journal of Science and Engineering)
The increasing significance of neighborhoods in many urban planning situations focus on the social aspect of creating sustainable communities and societies, underlines the necessity of developing socially sustainable neighborhoods. The neighborhood serves as a fundamental unit of society and plays a crucial role in developing the sustainability of the various urban areas. Undoubtedly, with sustainable neighborhoods the achievement of sustainable cities is possible. The focus of this research is the city of Erbil, located in the northern part of Iraq. This study aims to analyze the different characteristics related to the sustainability of the Saidawa neighborhood in the city of Erbil. Erbil is considered one of the city's attractive parts due to the diversity of residential, commercial, and other activities. The research presents the current state of the Saidawa neighborhood and compared to the five sustainable neighborhood principles established by UN-Habitat. The results showed that Saidawa neighborhood has a great potential for sustainability and the recommended approach is to manage potential development through urban planning. and building codes that accommodate transformations and offer innovative solutions that contribute to sustainable growth within the neighborhood.